1992
DOI: 10.1002/bip.360321211
|View full text |Cite
|
Sign up to set email alerts
|

Helix propagation in trifluoroethanol solutions

Abstract: Helix propagation of the S-peptide sequence (residues 1-19 of ribonuclease A) in 2,2,2-trifluoroethanol (TFE) solutions has been investigated with CD and nmr Overhauser effect spectroscopies. In this study, the S-peptide helix is covalently initiated at the N-terminus through disulfide bonds to a helix scaffold derived from the N-terminal sequence of the bee venom peptide apamin. The entire S-peptide sequence of this hybrid sequence peptide becomes helical at high proportions of TFE. Residues 14-19 of the S-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
3

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 17 publications
(2 reference statements)
8
76
3
Order By: Relevance
“…This behavior correlates well with the helix stop signal characterized in · this segment of the molecule (Rico, et al, 1983;Kim & Baldwin, 1984). It has recently been shown that the helix can be pushed through this stop signal by the presence of high TFE concentrations in the solvent (Storrs, et al, 1992). In the Apa-M5 hybrid, the helix seems to propagate further into the sequence, perhaps not terminating until the last residue.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…This behavior correlates well with the helix stop signal characterized in · this segment of the molecule (Rico, et al, 1983;Kim & Baldwin, 1984). It has recently been shown that the helix can be pushed through this stop signal by the presence of high TFE concentrations in the solvent (Storrs, et al, 1992). In the Apa-M5 hybrid, the helix seems to propagate further into the sequence, perhaps not terminating until the last residue.…”
supporting
confidence: 65%
“…compensated by the enthalpy of hydrogen bonds between water and the backbone amide proton or carbonyl groups in the random coiL This .competition by solvent hydrogen bonds is demonstrated by the formation of helices by short peptides in solvents containing trifl.uoroethanol (TFE). This solvent with a lower dielectric constant reduces the enthalpy ofTFE-backbone amide proton hydrogen bonds (Presta & Rose, 1988;Storrs, et al, 1992;Sonilichsen, et al, 1992), although the stabilizing effects ofTFE are entropic as well (Conio, et al, 1970). The unfavorable loss in entropy upon folding further contributes to the destabilization of short a-helices.…”
Section: The A-helixmentioning
confidence: 99%
“…However, earlier studies on the role of electrostatic interactions in the stability of the S-peptide from RNase A have shown that magnitude of the charged group effects is unaltered in the presence of TFE (Nelson & Kallenbach, 1986. A general mechanism by which TFE and other aliphatic alcohols could stabilize helices has been suggested (Conio et al, 1970;Storrs et al, 1992;Cammers-Goodwin et al, 1996). These authors suggest that TFE raises the free energy of the random coil state, because TFE-water mixtures are less able to solvate the amide group of the peptide backbone.…”
Section: Discussionmentioning
confidence: 99%
“…TFE is an extensively employed structure-stabilizing solvent (35,36). Upon TFE addition, a dramatic change in the CD spectra was observed, pointing at the induction of an ␣-helical conformation (supplemental Fig.…”
Section: Crt C-t Secondary Structure Ismentioning
confidence: 98%